tan 52 = 180/a; a = 180/tan 52
tan 43 = 180/b; b = 180/tan 43
you need to calculate, a-b = 180/tan 52 - 180/tan 43
substitute the value of tan thetas, and calculate it simply...
Answer:
3
Step-by-step explanation:
could the length of the first triangle to the length of the second triangle
Based on the mass of the circle and the triangle, we can find the mass of the square to be<u> 3.33 grams</u>
<h3>Mass of each side of hanger </h3>
Assuming the mass of the square is x, the equation for the first side is:
= (3 x mass of circle) + (2 x mass of triangle) + (6 x mass of square)
= ( 3 x 2) + ( 2 x 4) + ( 6 × x)
= 6 + 8 + 6x
Mass of other side:
= (2 x mass of circle) + (5 x mass of triangle) + (3 x mass of square)
= ( 2 x 2) + ( 5 x 4) + ( 3 × x)
= 4 + 20 + 3x
<h3>Mass of square </h3>
As both sides are equal, equate both formulas to find x:
6 + 8 + 6x = 4 + 20 + 3x
6x - 3x = 24 - 14
3x = 10
x = 10/3
x = 3.33 grams
In conclusion, each square is 3.33 grams.
Find out more on problems requiring equating at brainly.com/question/20213883.
-21 - (-13)
-21 + 13
= -8
The answer B)